Basal Forebrain Cholinergic System and Orexin Neurons: Effects on Attention - Villano, Ines; Messina, Antonietta; Valenzano, Anna; Moscatelli, Fiorenzo; Esposito, Teresa; Monda, Vincenzo; Esposito, Maria; Precenzano, Francesco; Carotenuto, Marco; Viggiano, Andrea; Chieffi, Sergio; Cibelli, Giuseppe; et al. (Frontiers in Behavioral Neuroscience, 2017)
The basal forebrain (BF) cholinergic system has an important role in attentive functions. The cholinergic system can be activated by different inputs, and in particular, by orexin neurons, whose cell bodies are located within the postero-lateral hypothalamus. Recently the orexin-producing neurons have been proved to promote arousal and attention through their projections to the BF. The aim of this review article is to summarize the evidence showing that the orexin system contributes to attentional processing by an increase in cortical acetylcholine release and in cortical neurons activity.